Study on flexural performance of fabricated natural fiber hybrid polypropylene composite: an experimental investigation through designed experiments. (10th June 2019) - Kumar, Rajendra; Singh, Ravi Pratap; Kataria, Ravinder
Abstract : Purpose: This paper aims to investigate the flexural properties i.e. the flexural strength and the flexural modulus under the influence of selected input variables, namely; fiber type, fiber loading and fiber size in fabricated natural fiber polymeric composites through using Taguchi's design of experiment methodology. Design/methodology/approach: The Taguchi's design of experiment approach has been used to scheme a suitable combination to fabricate the polymeric composites. Pure polypropylene (PP) has been chosen as a matrix material, whereas two types of fibers, namely; wood powder (WP) i.e. sawdust and rice husk powder (RHP), have been used as a reinforcement in the matrix. Microstructure analysis of fabricated and tested samples has also been evaluated and analyzed using a scanning electron microscope. This analysis has divulged that at moderate fiber size and higher fiber loading, no gap or cavities presented between the fillers and matrix particles, which illustrates the good interfacial bonding between the materials. Findings: The flexural strength of the wood powder pure polypropylene (WPPP) composite decreases if the fiber content gets increased beyond 20 Wt.%. In addition, the flexural strength of hybrid composite (WPRHPPP) has been revealed to get improved more in comparison to composites with single fiber as reinforcement. Furthermore, the flexural modulus of WPPP composite has also increased with the increase in fiber loading. It has been concluded that reinforcement size plays an imperative role in influencing the flexural modulus. The optimum parametric setting for the flexural strength and the flexural modulus has been devised as; fiber type – WPRHP, fiber loading – 10 Wt.% and fiber size – 600 µ m; and fiber type – WP, fiber loading – 30 Wt.% and fiber size – 1, 180 µ m, respectively. The microstructure images clearly revealed that during conducted flexural tests, some particles get disturbed from their bonded position that mainly represents the plastic deformation. Social implications: The fabricated polymer materials proposed in the research work are green and environmentally friendly. Originality/value: The natural fiber-based composites are possessing wide-spread requirements in today's competitive structure of manufacturing and industrial applications. The fabrication of the natural fiber-based composites has also been planned through the designed experiments (namely; Taguchi Methodology- L9 orthogonal array matrix), which, further, makes the analysis more fruitful and qualitative too. The fabricated polymer materials proposed in the research work are green and environmentally friendly. Shisham WP has been rarely used in the past researches; therefore, this factor has been included for the present work. The injection molding process is used to fabricate the three different polymer composite by varying the fiber weight percentage and fiber size.